Diabetes type 1 therapy individualization among children suffering from autism spectrum disorder Indywidualizacja terapii cukrzycy typu 1 u dzieci z zaburzeniami z kręgu autyzmu - Halla Kamińska; Przemysława Jarosz-Chobot (Termedia Publishing House, 2011)
Over the last years studies suggest an association between type 1 diabetes (DM1) and autism spectrum disorder (ASD). In this case study two children suffering from DM 1 and ASD were presented. Both are treated in the Centrum Zdrowia Dziecka in Katowice, Poland. The authors highligh everyday problems and challenges that patients, tutors and doctors have to face. The key to effective treatment is its individualization connected with proper education of the patient and his caregivers.